Three‐dimensional environment and vascularization induce osteogenic maturation of human adipose‐derived stem cells comparable to that of bone‐derived progenitors. (8th July 2020) - Ibrahim, Amel; Rodriguez‐Florez, Naiara; Gardner, Oliver F. W.; Zucchelli, Eleonora; New, Sophie E. P.; Borghi, Alessandro; Dunaway, David; Bulstrode, Neil W.; Ferretti, Patrizia
Abstract: While human adipose‐derived stem cells (hADSCs) are known to possess osteogenic differentiation potential, the bone tissues formed are generally considered rudimentary and immature compared with those made by bone‐derived precursor cells such as human bone marrow‐derived mesenchymal stem cells (hBMSCs) and less commonly studied human calvarium osteoprogenitor cells (hOPs). Traditional differentiation protocols have tended to focus on osteoinduction of hADSCs through the addition of osteogenic differentiation media or use of stimulatory bioactive scaffolds which have not resulted in mature bone formation. Here, we tested the hypothesis that by reproducing the physical as well as biochemical bone microenvironment through the use of three‐dimensional (3D) culture and vascularization we could enhance osteogenic maturation in hADSCs. In addition to biomolecular characterization, we performed structural analysis through extracellular collagen alignment and mineral density in our bone tissue engineered samples to evaluate osteogenic maturation. We further compared bone formed by hADSCs, hBMSCs, and hOPs against mature human pediatric calvarial bone, yet not extensively investigated. Although bone generated by all three cell types was still less mature than native pediatric bone, a fibrin‐based 3D microenvironment together with vascularization boosted osteogenic maturation of hADSC making it similar to that of bone‐derived osteoprogenitors. This demonstrates the important role of vascularization and 3D culture in driving osteogenic maturation of cells easily available but constitutively less committed to this lineage and suggests a crucial avenue for recreating the bone microenvironment for tissue engineering of mature craniofacial bone tissues from pediatric hADSCs, as well as hBMSCs and hOPs. Abstract : Human adipose‐derived stem cells (hADSCs) are a more accessible source of cells for bone tissue engineering but limited by immature osteogenic differentiation capacity. This study demonstrates that three‐dimensional microenvironment and early vascularization promote osteogenic maturation achieved by hADSC comparable to calvarial bone‐derived precursor cells such as human bone marrow‐derived mesenchymal stem cells (hBMSCs) and human osteoprogenitor cells (hOPs).